A educação brasileira nas composições do rap nacional - Jesus, Pedro Henrique da Costa Carvalho de (2020)
This research aimed to analyze the references about school and education contained in the Brazilian rap lyrics, covering the productions from the 1980s to the present times, in order to relate them to the political and social transformations in the country. This analysis was intended to contribute to studies on the relationship between education and society, by trying to understand what a part of the Brazilian population elaborates about the school, especially the young residents of the peripheries in large cities, who express themselves through the rap music. The analysis focused on discussing important issues to the critique of the present, as well as the debates about race, class and their social mobilizations. Throughout this investigation, different survey and research procedures were adopted, which resulted in the elaboration of a rich database containing 102 songs. A large number of references about the Brazilian education was found in the lyrics of rap, as well as a variety of themes related to it, such as social inequality, racial issues, violence, among others. An analysis of the content of the lyrics was carried out based on the theoretical framework of the Critical Social Theory, especially the concepts related to culture and education, such as cultural formation and pseudoformation, by Theodor Adorno, through which it was possible to perform different articulations using the analyzed material